Climate risk mapping provides rice growers with adaptation options in the Mekong River Delta - Yen, Bui Tan (2019)
The Mekong River Delta in Vietnam accounts for over half of the country’s domestic #rice production yet is increasingly affected by climate change. Dr. Bui Tan Yen is leading a team to develop an approach known as CS-MAP, a participatory approach of climate risk mapping, which provides farmers with adaptation options.